Sensitivity Analysis in Pension Expenditure Model - Sapiri, Hasimah; Kamil, Anton Abdulbasah; Mat Tahar, Razman
This paper describes a dynamics model of pension expenditure with particular case on Malaysia public employees’ pension plan. We analyzed pension expenditure due to salary and demographic risk. Then, sensitivity analysis was performed in order to validate the pension expenditure model